The influence of curing methods on the strength of MSWI bottom ash-based alkali-activated mortars: The role of leaching of OH− and free alkali. (20th October 2018) - Huang, Guodong; Ji, Yongsheng; Zhang, Linglei; Li, Jun; Hou, Zhihui
Highlights: Standard room curing is not suitable for alkali-activated materials. The resulting OH − and free alkali leaching severely affects strength development. Seal curing effectively prevents the leaching of OH − and free alkali. Abstract: This study investigated the influence of different curing methods on the strength development of municipal solid waste incinerator bottom ash alkali-activated mortars. The results showed that standard room curing is not suitable for alkali-activated materials. The main reason for this is the humidity > 95% in the curing room, which causes wet sample surfaces. This leads to OH − and free alkali leaching, which severely affects strength development. Soaking curing further aggravates this effect. However, seal curing effectively prevents the leaching of OH − and free alkali and thus maintains high alkalinity, which benefits the strength development. Therefore, the method of seal curing is more suitable for alkali-activated materials.